Genes involved in muscle lipid composition in 15 European Bos taurus breeds. (23rd April 2013) - Dunner, S.; Sevane, N.; Garcia, D.; Levéziel, H.; Williams, J. L.; Mangin, B.; Valentini, A.
Summary Consumers demand healthy and palatable meat, both factors being affected by fat composition. However, red meat has relatively high concentration of saturated fatty acids and low concentration of the beneficial polyunsaturated fatty acids. To select animals prone to produce particular fat types, it is necessary to identify the genes influencing muscle lipid composition. This paper describes an association study in which a large panel of candidate genes involved in adipogenesis, lipid metabolism and energy homoeostasis was tested for effects on fat composition in 15 European cattle breeds. Sixteen genes were found to have significant effects on different lipid traits, and among these, CFL1 and MYOZ1 were found to have large effects on the ratio of 18:2/18:3, CRI1 on the amount of neutral adrenic acid (22:4 n‐6), MMP1 on docosahexaenoic acid (22:6 n‐3) and conjugated linoleic acid, PLTP on the ratio of n‐6:n‐3 and IGF2R on flavour. Several genes – ALDH2, CHRNE, CRHR2, DGAT1, IGFBP3, NEB, SOCS2, SUSP1, TCF12 and FOXO1 – also were found to be associated with both lipid and organoleptic traits although with smaller effect. The results presented here help in understanding the genetic and biochemical background underlying variations in fatty acid composition and flavour in beef.